La noche se llama Olalla - Ferrero, Jesús, 1952- (Nuevos tiempos (Madrid, Spain) ;, 2013)
Detective Agatha Blanc sheds light on a young woman's tragic demise when Olalla Young's diary indicates her death may have been no accident. Now Agatha must sift through whispers of rape and drugs as she scours a Madrid stuck in the throws of postwar depression for answers surrounding the woman who carried so much more than a haunting name. Spain.